An Integrated Hydrodynamic and Pollutant Transport Model for the Nearshore Areas of the Great Lakes and Their Tributaries - Wu, Jian (My University, 1993)
This thesis deals with the modelling of the circulation and pollutant transport in the nearshore areas of lakes and their tributaries. An integrated hydrodynamic/pollutant transport model was developed which operates in an interactive environment and is equipped with powerful graphics. The model can predict: (a) the horizontal and vertical current structure in the lake under isothermal and stratified conditions for steady and variable wind conditions, (b) the spatial and temporal pollutant concentration distributions in the lake from multiple input pollutant sources such as creeks, sewer treatment plant outfalls (STPs) and combined sewer outfalls (CSOs) discharging in the lake, and (c) the particle trajectories released in different locations in the lake. The model was calibrated with extant laboratory data. The water level set-up and current structure in the Great Lakes were obtained under various wind conditions and in two cases, in Lake St. Clair and Lake Ontario, the model was verified with current meter and water elevation measurements, respectively. The model was successfully applied to the St. Clair River in Sarnia for a number of storm cases and was proven to be an effective tool in screening remedial options for mitigation of bacteriological pollution in the Bay. The field data collected during the 1990-1991 field season in Hamilton Harbour was analyzed and used to verify the model. The seiches of Lake Ontario and Hamilton Harbour were revealed for the first time in the water level data in the Harbour. The simulated and measured currents and drogue trajectories were in good agreement, indicating the presence of topographical eddies and mixing zones in the Harbour. Finally, a nested-grid model was developed and successfully applied in three nearshore areas of Hamilton Harbour to examine the impact of artificial islands by studying the changes in current patterns and concentration peak, exposure, and flushing time in different locations of concern.
Keywords: Civil Engineering; Civil Engineering